4,4′,5,5′-tetrakis(guanidinyl)binaphthyl - synthesis and properties of two redox-active ligands and oxidative C-C coupling to perylene derivatives - Wiesner, Sven; Ziesak, Alexandra Sabrina; Reinmuth, Matthias; Walter, Petra; Kaifer, Elisabeth; Wadepohl, Hubert; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2013)
We report the synthesis and properties of the new redox-active ligands 4,4′,5,5′-tetrakis(tetramethylguanidinyl)binaphthyl and 4,4′,5,5′-tetrakis(N,N′-dimethylethyleneguanidinyl)binaphthyl. The first dinuclear zinc complexes were prepared. Oxidative C-C coupling of these compounds leads to perylene derivatives.
Published Online: October 30, 2012
Gesehen am 08.11.2021